Prenatal restraint stress impairs recognition memory in adult male and female offspring. Issue 3 (29th June 2020) - Moura, Clarissa A.; Oliveira, Matheus C.; Costa, Layse F.; Tiago, Pamella R. F.; Holanda, Victor A. D.; Lima, Ramon H.; Cagni, Fernanda C.; Lobão-Soares, Bruno; Bolaños-Jiménez, Franscico; Gavioli, Elaine C.
Abstract: Objective: Accumulating evidence from preclinical and clinical studies indicates that prenatal exposure to stress impairs the development of the offspring brain and facilitates the emergence of mental illness. This study aims to describe the impact of prenatal restraint stress on cognition and exploration to an unfamiliar environment at adulthood in an outbred strain of mice. Methods: Late pregnant mice were exposed to restraint stress and adult offspring (60 days of age) behaviours were assessed in the object recognition task and open field test. Findings: Prenatal stress (PNS) impaired new object recognition in male and female mice. Importantly, the learning deficits in female PNS mice were linked to their estrous cycle. Actually, PNS females in metestrus/diestrus but not in proestrus/estrus phases displayed recognition deficits compared to controls. Concerning locomotion in an unfamiliar environment, male but not female PNS mice displayed significant increase, but showed no differences in the distance travelled within the centre zone of the arena. Conclusion: Present findings support the view that maternal restraint-stress during late pregnancy impairs recognition memory in both male and female offspring, and in females, this cognitive deficit is dependent on the estrous cycle phase. Ultimately, these data reinforce that PNS is an aetiological component of psychiatric disorders associated with memory deficits.